DEVELOPMENT OF SWEET BOILED MACKEREL IN SUGAR PALM SOUP IN RETORT POUCH - Klamsakul, Supatra; Siritanawong, Bunyat; Sriaumnouy, Bundidpong (Life Sciences and Environment Journal, 2019)
This research aimed to develop sweet-boiled mackerel product by using locally available palm sugar to replace and add value to the product by studying the recipes and process of sweet-boiled mackerel in sugar palm juice in retort pouch by replacing the most like standard recipes with fresh sugar palm juice to water into the sweetened mackerel soup at 0, 25, 50 and 75%.The results showed that the panelists preferred the replacement with 25% sugar palm juice: 75% water, with the highest like in all characteristics and liking score was in the range of 7.40-8.18. Sterilization at 121 °C for 30, 45 and 60 minutes had F0 values of 4.46, 17.25 and 29.55 minutes, respectively. The 45-minute sterilized sweet mackerel had the highest liking scores, by scoring in every characteristics at 6.66-8.26. As longer sterilization resulted in a darker brown color and a* value of mackerel and sweetened boiled soup were higher, but the L* value of both mackerel meat and sweetened boiled soup decreased. It was found that the longer heating increased the hardness of the mackerel meat but there was statistically significant difference (p ≤ 0.05). All the sterilization condition showed no total microorganism (Aerobic plate count), Clostridium botulinum, highly heat-resistant microorganisms (Thermophile anaerobe) and Flat sour thermophiles.